Effects of Optimized Acupuncture and Moxibustion Treatment on Depressive Symptoms and Executive Functions in Patients With Post-Stroke Depression: Study Protocol for a Randomized Controlled Trial - Luo, Meng; Duan, Zhaoyuan; Song, Xiaolei; Liu, Chengmei; Li, Ruiqing; Su, Kaiqi; Bai, Yanjie; Wang, Xiaodan; Fu, Wenbin; Gao, Jing; Feng, Xiaodong (Frontiers in Neurology, 2022)
Background Post-stroke depression (PSD), a common neuropsychiatric comorbidity after stroke, has a negative impact on the functional recovery and quality of life of survivors. It lacks effective therapeutic drugs with good curative effects and few adverse reactions. Preliminary experiments have shown that the optimized acupuncture and moxibustion treatment (OAMT), including acupuncture, moxibustion, and auricular intradermal acupuncture, improved depressive symptoms and neurological deficits in patients with PSD. However, the evidence for its effectiveness is still insufficient. Hence, we designed this study to evaluate the efficacy and safety of the OAMT in the treatment of PSD and to explore its possible mechanism from the perspective of executive functions. Methods/Design This is a randomized controlled trial, which comprises a total of 134 patients with PSD. Participants are randomized into intervention group and control group at a 1:1 ratio. All treatments are given five times per week for 4 weeks. The primary outcome is the severity of depression, which is evaluated by the Hamilton Depression Scale-17 (HAMD-17) and the Beck Depression Rating Scale (BDI). Secondary outcomes are executive abilities, which are measured by several neuropsychological tests, including the Stroop Color and Word Test (SCWT), the Trial Making Test (TMT), the Digit Symbol Substitution Test (DSST), and the Matrix Reasoning Test (MRT). All outcomes have been evaluated at baseline and weeks 4, 8, 12, and 20. At the same time, functional MRI (fMRI) is used to measure the functional connectivity in the cognitive control network (CCN) at baseline and 4 weeks after intervention. Discussion This study aims to provide high-quality evidence for the efficacy and safety of the OAMT for treating PSD. In addition, this trial is the first trial to explore if the improvement condition of depression in the OAMT group is related to the improvement of executive functions and the favorable changes in the structure. Clinical Trial Registration Chinese Clinical Trial Registry, identifier: ChiCTR2100048431.